First Population-Based Report of Infants with Congenital Diaphragmatic Hernia: 30-Day Outcomes from the American College of Surgeons National Quality Improvement Program - Zani-Ruttenstock, Elke; Zani, Augusto; Eaton, Simon; Fecteau, Annie (European Journal of Pediatric Surgery, 2019)
Aim The American College of Surgeons has developed a registry, the National Quality Improvement Program Pediatric (NSQIP-P), that provides participating centers with high-quality surgical outcome data for children. Herein, we aimed to analyze for the first time the short-term outcomes of live-born infants with congenital diaphragmatic hernia (CDH) registered on this large North American database.Methods During 2015 to 2016, up to 101 participating centers uploaded 95 perioperative data points on the NSQIP-P database for patients that underwent surgical repair of CDH. The demographics, peri-, and post-operative data (up to 30 days following surgical repair) of infants with CDH were reviewed. Binary logistic regression was performed to test associations between risk factors and mortality.Main Results There were 432 (61% male) infants, who underwent CDH surgical repair during the study period. The prematurity rate (gestational age < 37 weeks) was 17%. The majority of infants (82%) had cardiac risk factors identified (72% were reported as major/severe). Extracorporeal membrane oxygenation (ECMO) was employed in 13% of patients prior to surgery. The majority of infants (83%) were ventilated preoperatively, and 34% received inotropes. Median age at surgery was 5 (0–74) days. CDH repair was attempted via thoracoscopy in 18% (n = 79) infants, but with a high rate of conversion to open surgery (n = 32, 41%). The postoperative 30-day mortality rate was 9%. At binary logistic regression, major cardiac risk factors (odds ratio [OR], 1.7 [0.9–3.2], p = 0.095), Appearance, Pulse, Grimace, Activity, and Respiration at 1 minute (OR, 0.7 per unit [0.5–0.8], p < 0.005), and birth weight (OR, 0.5 per kg [0.2–1.0], p < 0.05) were retained in the final model as significantly associated with mortality.Conclusion This is the first report on CDH outcomes from the NSQIP-P database. Utilization of ECMO was low compared with single-center studies from North America. The early postoperative mortality rate of babies with CDH considered suitable for surgery remains high.
Keywords: congenital diaphragmatic hernia; short-term outcome; Bochdalek hernia; NSQIP; epidemiology